(untitled) (Journal of Vocational Innovation, Achievement and Education, 2026)
This study aimed to evaluate the feed management practices and nutritional adequacy of diets provided to grower phase Alope chickens at Hill Happy Farm, Barru Regency, South Sulawesi. Feed management and nutritional adequacy are essential factors influencing the growth, health, and productivity of Alope chickens, yet farm level information on this matter remains limited. The study was conducted over a two-week period in May 2026 using a descriptive evaluative method with a case study approach. Data were collected through direct observation and structured interviews with the farm owner. The nutrient composition of the ratio was calculated using feed composition tables from the literature and compared with the nutritional requirements for local breeder-grower chickens according to the Indonesian National Standard (SNI 7783-2:2022). The ratio consisted of rice bran (66.67%), yellow corn (16.67%), and layer concentrate (16.67%), given twice daily at inconsistent times (approximately 08:00-09:00 and 17:00-18:00). The daily feed allowance reached 266.67 g/bird/day, exceeding the recommended 80-100 g/bird/day. Crude protein (13.25%), metabolizable energy (2,053 kcal/kg), and available phosphorus (0.30%) were below standard, while crude fiber (13.25%) and calcium (1.55%) exceeded the recommended limits; only crude fat (4.92%) met the standard. These imbalances were consistent with field observations of feather loss in 20-30% of the chickens and several cases of weak bones. The feed management and ratio composition at Bukit Bahagia Farm did not meet the nutritional requirements of grower-phase Alope chickens. Reformulating the ratio by reducing rice bran, increasing corn and high-quality protein sources, and adding vitamin-mineral premix, phytase, and synthetic amino acids is recommended to improve nutritional adequacy, health, and productivity.